2019
DOI: 10.3389/fpsyg.2019.00054
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Morphological Awareness and Reading Comprehension Among Chinese Children

Abstract: The present study examined the developmental relationship between morphological awareness and reading comprehension, using a 1-year longitudinal study with a sample of 439 Chinese-speaking students in Grades 1, 3, and 5, respectively. Children’s text reading and three components of morphological awareness: homophone awareness, homograph awareness and compounding awareness were measured. After controlling for word reading, vocabulary knowledge, IQ, rapid automatized naming and phonological awareness measured at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 47 publications
1
12
0
Order By: Relevance
“…Each participant received a small gift for taking part. Reading skill was assessed as part of a larger project using standard tests of reading comprehension (Xie, Zhang, Wu, & Nguyen, 2019) and reading fluency (Li & Wu, 2015;Xue et al, 2013). Participants were selected from Grade 5 as this age-group would be expected to have basic metalinguistic knowledge (reading fluency, vocabulary, comprehension skills) required to read and understand sentences (Xue et al, 2013).…”
Section: Participantsmentioning
confidence: 99%
“…Each participant received a small gift for taking part. Reading skill was assessed as part of a larger project using standard tests of reading comprehension (Xie, Zhang, Wu, & Nguyen, 2019) and reading fluency (Li & Wu, 2015;Xue et al, 2013). Participants were selected from Grade 5 as this age-group would be expected to have basic metalinguistic knowledge (reading fluency, vocabulary, comprehension skills) required to read and understand sentences (Xue et al, 2013).…”
Section: Participantsmentioning
confidence: 99%
“…Multiple skills, including both language and cognitive skills, contribute to the three sub-processes of reading ( Hannon and Daneman, 2001 ; Perfetti et al, 2007 ; Oakhill, 2020 ). Specifically, language skills, including phonological knowledge, morphological knowledge, vocabulary knowledge, and orthographic knowledge, are important word-level skills in the process of building surface structure ( Ehri, 2014 ; Quinn et al, 2015 ; Xie and Wu, 2019 ; Liu and Liu, 2020 ). In the textbase representation process, the language skill of syntactic knowledge is essential as it helps readers to group words, trace the logical and semantic relations among linguistic constituents, and build initial propositions ( So and Siegel, 1997 ; Cheung et al, 2007 ; Brimo et al, 2018 ; Simpson et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“… 23 Thus, compounding awareness could help children to take in the meanings of novel and complex words within texts thereby helping them to understand the meaning of the whole passage. 61 Notably, morphological awareness shares characteristics with phonological and orthographic awareness, syntactic awareness (the morphological structure of words is often conditioned by syntactic context), and semantic knowledge in Chinese. 32 Extensive research showed that morphological awareness was a stronger correlate of reading comprehension than phonological awareness in Chinese.…”
Section: Instructionmentioning
confidence: 99%